Rectus femoris activation is modified by training status and correlates with endurance performance in cycling - Dutra, Y. M.; Lopes, V. H. F.; Brisola, G. M. P.; Diefenthaeler, F.; Zagatto, A. M. (Sport Sciences for Health, 2022)
The study aimed to compare the activity of low and fast-twitch muscle fibers of the prime mover muscles used in cycling between recreational cyclists with different training levels during a high-intensity exercise. Twelve male cyclists performed, on distinct days, a graded exercise test and two bouts of cycling at severe-intensity. The first bout was performed as familiarization and the second to monitor the muscle activation through surface electromyography (EMG) of the rectus femoris, vastus lateralis, biceps femoris, and gluteus maximus. According to peak oxygen uptake (VO2peak) and maximal aerobic power (MAP), participants were classified as untrained (VO2peak = 43.5 ± 1.2mL kg-1 min-1, MAP = 3.3 ± 0.1W kg-1) or recreationally trained (VO2peak = 53.7 ± 2.9mL kg-1 min-1, MAP = 4.4 ± 0.4W kg-1). During high-intensity exercise, the recreationally trained group presented higher area under the root mean square curve (p = 0.013, statistical power = 77%) and high-frequency content (p = 0.045, statistical power = 70%) for the rectus femoris EMG signal compared to the untrained group. Significant correlations (p = 0.050) were observed between these EMG parameters and VO2peak (r = 0.610), MAP (r = 0.647), and respiratory compensation point intensity (r = 0.833). We conclude that overall and fast-twitch motor unit recruitment capacity of the rectus femoris is modified by the endurance training status and may play an important role in aerobic fitness level in cycling.